Does"Evidence-Based Policy" Help Protect LGBT Rights? A View from U.S. Social Work - Stephen Edward McMillin (Social Work and Society)
Activists who work for LGBT (lesbian, gay, bisexual, and transgendered) equality frequently claim such equality to be a matter of human and/or civil rights and therefore organize their legal activism accordingly.Â  However, U.S. courts have often failed to acknowledge these rights or to recognize LGBT persons as a legal class.Â  In this essay, Stephen Edward McMillin discusses the current emphasis on evidence based policy and practice in child and family social work, arguing that this approach has been pragmatically effective in advancing LGBT rights to adopt and foster children even when LGBT human and civil rights remain formally unacknowledged in much of U.S. law.